OBTENÇÃO DE COMPOSTOS DE POLIPROPILENO COM PECTINA CÍTRICA - Ribeiro, Kairin Cristine (2014)
Researches based on the mixture of synthetic with natural polymers have intensified in recent times. The idea of using polysaccharides nano or micro level with polyolefins is the new of this work. Three compositions of polypropylene and commercial citrus pectin was prepared in proportions of 1, 3 and 5%. A coupling agent was used, the graphitized polypropylene with maleic anhydride to advance interaction between natural and synthetic particles. The obtaining of particles in nanometric scale pectin was made from colloid mill grinding. Some particles arrived near 100nm and majority the particles reached scales around 300nm. The structural analysis by X-ray diffraction and Fourier transform infrared spectroscopy demonstrated an interaction between maleic anhydride and pectin despite clusters of hydrophilic particles that were seen by scanning electron microscopy In the X-ray diffraction, the presence of crystals of sugars were detected. These crystals may have caramelized because processing temperatures are close to 200 C and were detected by colorimetry. Based on the mechanical data, it is possible realize that pectin had a plasticizing effect on the synthetic polymer, corroborating the rheological data and thermogravimetric tests, considering that the addition of higher amount of particles produces more thermal stability of the synthetic polymer.